Infection control in child daycare centers: logistics, knowledge, and practices of caregivers - Mohamed Mostafa Tahoun; Ali Abdel Halim Hasab; Nessrin Ahmed El-Nimr (SpringerOpen, 2019)
Abstract Background Children attending daycare centers (DCCs) are at high risk of contracting infectious diseases due to several factors including lack of knowledge among the caregivers about infection prevention and control practices. The objectives were to describe the DCC features, infrastructure, and infection control logistics, to assess knowledge of DCC caregivers regarding infectious diseases, and to assess their infection control practices. Methods Using a cross-sectional design, 402 caregivers working in 59 DCCs in three districts in Alexandria, Egypt were included. Data were collected using a data collection sheet about the DCC features, a structured interviewing questionnaire to collect data on caregivers' personal characteristics, knowledge about infectious diseases, and the best infection control practices and an observational infection control practices checklist. Multiple analysis of variance was used to test the difference in two or more vectors of means (mean knowledge scores about infectious diseases and about infection control). Post hoc test using Tukey Honest Significant Difference was used to determine which groups in the sample differ. Regression analysis models were used to identify factors affecting knowledge score of caregivers, and to estimate the magnitude of the association between different variables and the level of practice of caregivers (poor/fair and good). Results Satisfactory features of the DCCs included the aeration, level of cleanliness, and availability of hand washing facilities, while the availability of gloves and aprons, alcohol-based products, and medical examination rooms were not satisfactory. Only 2.5% of caregivers had a good level of knowledge. Level of education was the only factor statistically associated with the level of knowledge. About 31% and 17% had poor and good practice score percent, respectively. District and daily working hours were the only variables statistically associated with the level of practice. Conclusion The level of knowledge and practice of caregivers was below optimum.